Analysis of Plenary Accord N° 676/2020: the dismissal of Oscar Ugarteche’s homosexual marriage lawsuit - Shinno Pereyra, Vanessa Elizabeth (2022)
The following work focuses on making an analysis on the against votes of the magistrates that dismissed the amparo process presented by Oscar Ugarteche, who pretended the Peruvian National Registry of Identification and Civil Status — RENIEC to register his marriage certificate, which took place in Mexico and was legally performed there, whilst not pretending the Peruvian State to recognize the legality of same-sex marriage.